2019
DOI: 10.3389/fpsyg.2019.02750
|View full text |Cite
|
Sign up to set email alerts
|

By Reverence, Not Fear: Prestige, Religion, and Autonomic Regulation in the Evolution of Cooperation

Abstract: Recent evolutionary theories of religions emphasize their function as mechanisms for increasing prosociality. In particular, they claim that fear of supernatural punishment can be adaptive when it can compensate for humans' inability to monitor behavior and mete out punishment in large groups, as well when it can inhibit individuals' impulses for defection. Nonetheless, while fear of punishment may inhibit some antisocial behaviors like cheating, it is unlikely to motivate other prosocial behaviors, like helpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Within polyvagal theory, parasympathetic activity also facilitates pro-social behaviors and social engagement (Porges, 2001 , 2007 ). Later work adapted the polyvagal theoretical framework, arguing that parasympathetic-mediated behaviors were necessary for the evolution of human prestige hierarchies (Lenfesty & Morgan, 2019 ). Indeed, parasympathetic activity has been linked to behaviors relevant to prestige based hierarchies – including social engagement, emotional and behavioral regulation, and compassion, among other pro-social behaviors (Bornemann et al, 2016 ; Miller et al, 2016 ; Roos et al, 2017 ; Segerstrom et al, 2011 ; Smith et al, 2020 ) – but parasympathetic activity has not been linked explicitly to trait prestige.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within polyvagal theory, parasympathetic activity also facilitates pro-social behaviors and social engagement (Porges, 2001 , 2007 ). Later work adapted the polyvagal theoretical framework, arguing that parasympathetic-mediated behaviors were necessary for the evolution of human prestige hierarchies (Lenfesty & Morgan, 2019 ). Indeed, parasympathetic activity has been linked to behaviors relevant to prestige based hierarchies – including social engagement, emotional and behavioral regulation, and compassion, among other pro-social behaviors (Bornemann et al, 2016 ; Miller et al, 2016 ; Roos et al, 2017 ; Segerstrom et al, 2011 ; Smith et al, 2020 ) – but parasympathetic activity has not been linked explicitly to trait prestige.…”
Section: Discussionmentioning
confidence: 99%
“…In one experiment, trait prestige, on its own or in an interaction with exogenous testosterone, did not predict cortisol responses to social evaluative stress in men, although trait prestige did correlate with reduced negative affect in this experiment 2 (Knight et al, 2017 ). Considering other physiological systems, some theorizing suggests the evolution of the parasympathetic nervous system may have been critical for the development of socially-binding behaviors inherent to human prestige hierarchies, such as social engagement and emotional and behavioral regulation (Lenfesty & Morgan, 2019 ; Porges, 2001 , 2007 ). Robust parasympathetic nervous system activity has, in turn, been associated with extensive health benefits (Kemp & Quintana, 2013 ; O’Connor et al, 2021 ; Thayer et al, 2012 ; Williams et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis across 18 societies clearly concluded that the effectiveness of punishment in promoting cooperation depends on the level of trust ( Balliet and Van Lange, 2013 ). Moreover, because human physiology has separate neurological systems for responding to threats and facilitating social interactions, fear of punishment may inhibit some anti-social behaviors like cheating, but still not motivate prosocial behavior ( Lenfesty and Morgan, 2019 ). In cases where players must have a personal commitment to fulfill their role, self-regarding actors who treat social norms as purely instrumental behave in a socially inefficient manner ( Gintis, 2014 , pp.…”
Section: Game Theory’s Basic Moral-psychological Assumptionsmentioning
confidence: 99%
“…Examples of such social learning biases include copying the majority (conformity), copying older individuals, copying when uncertain, or copying prestigious individuals [6]. In this study we focus on the latter: prestige-biased social learning (henceforth prestige-bias), which occurs when learners preferentially learn from individuals who are copied by others, attended to by others, or who generally receive freely conferred deference from others [7][8][9][10][11][12][13][14]. These individuals are said to have 'prestige'.…”
Section: Introductionmentioning
confidence: 99%